Upacara Sapuh Leger Sebagai Aplikasi Ajaran Manusa Yadnya di Lingkungan Padang Griya Kelurahan Padangsambian Denpasar Barat - Ratih, Ida Ayu; Dharma Putra, Anggara Putu; Laksana Utama, Putu Kussa (Institut Hindu Dharma Denpasar, 2019)
In Hindu, someone who is born to coincide with wuku wayang is a child who falls into the category of